RISK ASSESSMENT FOR ENHANCING THE EFFECTIVENESS OF TEXTILE INDUSTRY ENTERPRISES - Bahadirov Numonkhan Kamolkhanovich (American Journals, 2023)
As a result of the research carried out in this article, the main stages of the qualitative analysis of the risks arising in the improvement of the efficiency of the textile and clothing industry are formed and based. Also, their brief descriptions are given and specific features of qualitative risk analysis are described.
Keywords: textile industry, efficiency, risk analysis, risk, assessment.